2011
DOI: 10.1093/nar/gkr702
|View full text |Cite
|
Sign up to set email alerts
|

dsRNA expression in the mouse elicits RNAi in oocytes and low adenosine deamination in somatic cells

Abstract: Double-stranded RNA (dsRNA) can enter different pathways in mammalian cells, including sequence-specific RNA interference (RNAi), sequence-independent interferon (IFN) response and editing by adenosine deaminases. To study the routing of dsRNA to these pathways in vivo, we used transgenic mice ubiquitously expressing from a strong promoter, an mRNA with a long hairpin in its 3′-UTR. The expressed dsRNA neither caused any developmental defects nor activated the IFN response, which was inducible only at high exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
69
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(86 citation statements)
references
References 73 publications
13
69
0
Order By: Relevance
“…Although the preponderance of evidence therefore indicates that mammalian somatic cells are unable to produce functionally significant levels of siRNAs, this does not appear to be true for mouse germ cells and embryonic stem (ES) cells, which can produce readily detectable and biologically active levels of siRNAs from long dsRNA substrates (8)(9)(10)(11)(12). This observation suggested that these undifferentiated murine cells might express an alternative isoform of Dicer that had acquired the ability to effectively cleave long dsRNAs.…”
mentioning
confidence: 99%
“…Although the preponderance of evidence therefore indicates that mammalian somatic cells are unable to produce functionally significant levels of siRNAs, this does not appear to be true for mouse germ cells and embryonic stem (ES) cells, which can produce readily detectable and biologically active levels of siRNAs from long dsRNA substrates (8)(9)(10)(11)(12). This observation suggested that these undifferentiated murine cells might express an alternative isoform of Dicer that had acquired the ability to effectively cleave long dsRNAs.…”
mentioning
confidence: 99%
“…In particular, long dsRNAs have been reported by several groups to be processed into siRNAs in mouse oocytes and ES cells, and these siRNAs appeared fully capable of repressing target gene expression (13)(14)(15). Strikingly, mice engineered to transcribe a long inverted repeat were able to process the resultant dsRNA into functional siRNAs in oocytes but not in somatic cells (7). More recently, mouse ES cells infected with RNA viruses were found to express siRNAs of viral origin that were loaded into RISC and appeared to partially attenuate virus replication (16).…”
Section: Detection Of Sirnas In Murine Oocytes and Embryonic Stem Cellsmentioning
confidence: 99%
“…Of note, while insects express two Dicer proteins that mediate either miRNA or siRNA biogenesis, mammalian somatic cells express only one full-length Dcr isoform, Dcr S , that is incapable of producing significant levels of siRNAs, though it is, like insect Dcr1, fully competent for premiRNA processing (16,18) (Table 1). However, in an as-yet-undefined subset of undifferentiated rodent cells, including oocytes and ES cells and possibly including some other types of stem cells (7,(13)(14)(15)(16)(17)(18)(19), long dsRNAs can give rise to functional siRNAs, and these appear able to attenuate viral infections (Table 1). This appears to reflect the expression in these cells of a distinct, aminoterminally truncated isoform of Dicer, Dcr O , which has acquired the ability to effectively process long dsRNAs into siRNAs due to loss of an inhibitory domain present in the full-length Dcr S protein (17).…”
Section: Antiviral Rna Interference In Mammals: a Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Endo-siRNAs regulate gene expression through their duplexes with AGO2. Only one of the two strands, the 'guide' strand, is incorporated into the multi-protein RNAinduced silencing complex (RISC); the other ('passenger') strand is discarded (Tam et al 2008;Czech and Hannon 2011;Nejepinska et al 2012). The guide strand recognises a target mRNA by Watson-Crick base pairing and based on the degree of sequence complementarity between the siRNAs and target mRNA, either endonucleolytic cleavage or translational repression of the target mRNA follows (Carthew and Sontheimer 2009).…”
Section: Introductionmentioning
confidence: 99%